The 2020 IDS Release of the Antwerp COR*-Database. Evaluation, Development and Transformation of a Pre-Existing Database - Sam Jenkinson; Francisco Anguita; Diogo Paiva; Hideko Matsuo; Koen Matthijs (Historical Life Course Studies)
The Antwerp COR*-IDS database 2020 is a transformed and harmonized historical demographic database in a cross-nationally comparable format designed to be open and easy to use for international researchers. The database is constructed from the 2010 release of the Antwerp COR*-historical demographic database, which was created using a letter sample of the whole district of Antwerp (Flanders, Belgium). It has a total sample size of +/- 33,000 residents of Antwerp. The sample spans nearly seven decades. The data is collected from historical records: including population registers and vital registration records covering births, marriages, in/external migrations and deaths. The database covers up to three linked generations (in some cases more), and contains micro-data on individual level life courses, and relationships deriving from addressbased household composition methods. An important characteristic is the sample's large migrant population, including the timings of their demographic events and living arrangements, whilst resident in the district of Antwerp. In addition, the sample also contains a large array of occupational level information. This paper presents the processes, methodologies and documentation regarding the evaluation and development of a pre-existing historical database. This includes the systematic evaluation of the original samples, methodologies for address based reconstructing of households, and the geocoding of a historical database which took place during the current development of this new version of the database.